Kemampuan pemahaman matematis siswa MTs pada materi statistika ditinjau berdasarkan teori Newman - Andriani, Nurfitri; Purwasih, Ratni (IKIP Siliwangi, 2024)
The purpose of this study was to determine the extent to which students solve problems in mathematical understanding skills in statistics material. The method in this study is descriptive qualitative and data collection is given 3-point statistics questions in the form of descriptions. The research subjects were class VIII which amounted to 6 people. The results of the researcher's analysis show that mathematical understanding ability is still low in statistics material. Some of the difficulties experienced by students are that students still have difficulty reading the questions given, students' ability to understand the problem is still lacking, students' difficulty in writing the formula given, students' lack of accuracy in prerequisite material, students answer questions carelessly, so students do not solve the problem correctly. Difficulties in this study can be caused by students not paying attention to the teacher's explanation and even still lacking accuracy in understanding the problem, reading questions in the form of description questions, the way students think about mathematics comprehension skills is still difficult. Therefore, it is necessary to have an improvement and follow-up in future research to improve students' mathematical understanding ability in statistics material or better yet, it can replace other materials.